2022
DOI: 10.1007/s40120-022-00358-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Utilization and Expenditure Across Multiple Sclerosis Disease-Modifying Therapies: A Retrospective Cohort Study Using Claims Data from a Commercially Insured Population in the United States, 2010–2019

Abstract: Introduction Comparisons of healthcare utilization and expenditure among multiple sclerosis (MS) disease-modifying therapies (DMTs) are limited. Methods In this retrospective cohort study using commercial insurance claims data of a US population (2010–2019), we compared healthcare utilization and costs in MS across different DMTs. We assigned patients to different treatment arms: no DMT (ND), high-efficacy (HE) DMT (alemtuzumab, B cell depletion, cladribine, and nataliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This need is particularly urgent in chronic neurological diseases such as multiple sclerosis (MS) given their disproportionally high socioeconomic burden (Fattore et al, 2012;Hartung, 2021;Jennum et al, 2012;Zhu et al, 2022) and modifiable disease course (Giovannoni, 2018;Goldschmidt and McGinley, 2020). Low SES or proxy measures of SES in people with MS (pwMS) is associated with increased risk of MS (Bjørnevik et al, 2016a;Briggs et al, 2015Briggs et al, , 2014Dobson et al, 2020), worsening disability (Briggs et al, 2019;Calocer et al, 2020;D'hooghe et al, 2016;Harding et al, 2019), decreased access to neurological care (Contentti et al, 2019;Minden et al, 2008;Moss et al, 2020;Roddam et al, 2019), and lower quality of life (Boogar et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This need is particularly urgent in chronic neurological diseases such as multiple sclerosis (MS) given their disproportionally high socioeconomic burden (Fattore et al, 2012;Hartung, 2021;Jennum et al, 2012;Zhu et al, 2022) and modifiable disease course (Giovannoni, 2018;Goldschmidt and McGinley, 2020). Low SES or proxy measures of SES in people with MS (pwMS) is associated with increased risk of MS (Bjørnevik et al, 2016a;Briggs et al, 2015Briggs et al, , 2014Dobson et al, 2020), worsening disability (Briggs et al, 2019;Calocer et al, 2020;D'hooghe et al, 2016;Harding et al, 2019), decreased access to neurological care (Contentti et al, 2019;Minden et al, 2008;Moss et al, 2020;Roddam et al, 2019), and lower quality of life (Boogar et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The available MS disease-modifying therapies (DMTs) pose soaring costs and exhibit variable real-world effectiveness in preventing inflammatory disease activity and delaying disability worsening. [5][6][7] In the current practice, clinicians primarily rely on history, exams and neuroimaging to assess MS disease activity, disability progression, and treatment response. There is an unmet need to improve disease monitoring at the point of care to guide individualized management.…”
Section: Introductionmentioning
confidence: 99%
“…High utilization of DMTs in our population could be due to the fact that access to healthcare and medications in Saudi Arabia is for free and does not apply any restrictions, whereas the annual cost for DMTs in pwMS in the US exceeds 70,000$ (12). Zhu et al (11) also found that patients on HE or ME DMTs had more relapses than those left untreated. There are conflicting reports in literature as it pertains to the effect of DMT on ED visits; One study in British Columbia, Canada, investigated the use of DMT and its relation to the frequency of visits to the ED and found similar numbers on both arms of comparison as 58.0% of DMT users visited the ED whereas 55.6% of DMTs non-users visited the ED (9).…”
Section: Discussionmentioning
confidence: 95%
“…Using commercial insurance and Medicare Advantage claims, Zhu et al (11) conducted a US study which included 25,932 pwMS and found that 48.9% of patients were on a DMT. In contrast, 84.3% of our patients were on a DMT.…”
Section: Discussionmentioning
confidence: 99%